Volatile flavor constituents of fresh and processed kalamansi (Citrus microcarpa Bunge) juice - Mina, Cynthia P.
The volatile flavor constituents of kalamansi (Citrus microcarpa Bunge) juice was studied by combination of gas chromatoggraphic and sensory analyses; and changes in chemical and sensory characteristics of the juice were followed in the fresh, freshly processed and stored juices. Analysis of the volatiles in the headspace of the bottled juice at isopthermal gas chromatographic conditions gave 15 peaks, 6 of which were tentatively identified as acetaldehyde, acetone, ethanol, propanol, acetic acid and limonene, the latter amounting to 89.40% of the volatiles in the headspace. A larger number of constituents were separated and isolated from the total volatiles of the juice using temperature-programmed gas chromatography. A maximum of 59 peaks were resolved, the first 20 being similar to those of the headspace volatiles but were barely detected since they appeared in relatively minute amounts. As in the headspace analysis, limone was identified as the major component, making up 88.084% of the total volatiles in the fresh juice. Of the rest, the following flavor constitents were tentatively identified in addition to those same ones identified in the heaspace of the juice; linalool, terpinene-4-ol, terpineol, citronellol and geraniol. The oxygentated compounds, terpineol and terpinene-4-o1 were attributed to cause the increase the increase in intensities of the cooked and chemical notes of the juice storage but more markedly after the pasteurization step. In general, it was observed that although changes were not very marked at the storage periods, there were significant alterations in the freshly processed juice with regards to the relative % volatiles as well as its sensory attributes.